Screening of human LPHN3 for variants with a potential impact on ADHD susceptibility - Domene, Sabina (2011)
Attention deficit hyperactivity disorder (ADHD) is the most common behavioral disorder in childhood, and often has effects detectable into adulthood. Advances in genetic linkage and association analysis have begun to elucidate some of the genetic factors underlying this complex disorder. Recently, we identified LPHN3, a novel ADHD susceptibility gene harbored in 4q, and showed that a LPHN3 common haplotype confers susceptibility to ADHD and predicts effectiveness of stimulant medication. Here we present the mutational analysis of the entire coding region of LPHN3 in a cohort of 139 ADHD subjects and 52 controls from across the USA. We identified 21 variants, of which 14 have been reported and 7 are novel. These include 5 missense, 8 synonymous, and 8 intronic changes. Interestingly, neither susceptibility nor protective haplotype alleles are associated with obviously significant coding region changes, or canonical splice site alterations, suggesting that non-coding variations determining the quantity and/or quality of LPHN3 isoforms are the likely contributors to this common behavioral disorder.